Transtornos alimentares: fundamentos históricos Eating disorders: historical background - Táki Athanássios Cordás; Angélica de Medeiros Claudino (Brazilian Journal of Psychiatry, 2002)
Os autores fazem uma breve revisão dos aspectos históricos dos transtornos alimentares. Possíveis correlaçes psicopatológicas com os conceitos diagnósticos atuais são discutidas. The authors make a brief review of the historical aspects of eating disorders. Possible correlations with modern psychopathological aspects are commented